Bioreactor as the root cause of the “manganese effect” during Aspergillus niger citric acid fermentations - Fekete, Erzsébet; Bíró, Vivien; Márton, Alexandra; Bakondi-Kovács, István; Németh, Zoltán; Sándor, Erzsébet; Kovács, Béla; Fábián, István; Kubicek, Christian P.; Tsang, Adrian; Karaffa, Levente (Frontiers in Bioengineering and Biotechnology, 2022)
High-yield citric acid production by the filamentous Ascomycete fungus Aspergillus niger requires a combination of extreme nutritional conditions, of which maintaining a low manganese(II) ion concentration (<5 ug L-1) is a key feature. Technical-scale production of citric acid predominantly uses stainless-steel tank fermenters, but glass bioreactors used for strain improvement and manufacturing process development also contain stainless steel components, in which manganese is an essential alloying element. We show here that during citric acid fermentations manganese(II) ions were leaching from the bioreactor into the growth media, resulting in altered fungal physiology and morphology, and significant reduction of citric acid yields. The leaching of manganese(II) ions was dependent on the fermentation time, the acidity of the culture broth and the sterilization protocol applied. Manganese(II) ion leaching was partially mitigated by electrochemical polishing of stainless steel components of the bioreactor. High concentrations of manganese(II) ions during early cultivation led to a reduction in citric acid yield. However, the effect of manganese(II) ions on the reduction of citric acid yield diminished towards the second half of the fermentation. Since maintaining low concentrations of manganese(II) ions is costly, the results of this study can potentially be used to modify protocols to reduce the cost of citric acid production.